CLAUDE DEBUSSY’S VOCAL MINIATURE «CLAIR DE LUNE»: FROM AUTHORIAL CONCEPT TO PERFORMATIVE INTERPRETATIONS - Redya, Valentyna; Rakhmatullaieva, Angelina (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
Relevance of the study. Claude Debussy’s vocal music holds particular interest as a space where the composer developed his individual style. In these works, the “pioneer of 20th-century music” explored ways of conveying poetic imagery through sound, making the study of expressive means in his vocal miniatures vital for understanding his early creative evolution. Equally important is the performance aspect — particularly, the influence of French phonetics on vocal diction. Attention to the phonetic and prosodic features of the French language in singing allows for a deeper and more authentic interpretation of Debussy’s works, thus renewing interest in his vocal legacy today. Objective of the study. To reveal Debussy’s artistic intent in Clair de lune and examine how it is embodied in various performance interpretations. Methodology. The research employs a comprehensive approach, combining culturalhistorical, genre-stylistic, and intonational analysis with phonetic, comparative, and theoretical methods. These enable contextualization of the work, detailed musical and textual examination, and comparative evaluation of different interpretive approaches. The main results and conclusions. Clair de lune, based on a poem by Paul Verlaine, reflects Debussy’s enduring fascination with lunar imagery. Its refined melodicism, fluid rhythm, and rich harmonies create an atmosphere of serene dreaminess. A comparative analysis of interpretations by French soprano Natalie Dessay and Korean singer Anna Sohn reveals differences in phrasing, tempo, articulation, and dynamic shaping. While both demonstrate high artistic quality, Dessay’s native fluency in French ensures effortless, idiomatic expression of Verlaine’s “music of the word.” Sohn’s performance, more deliberate and carefully articulated, reflects the effort required to sing in a foreign language. The study shows that national vocal traditions and language proficiency play a significant role in shaping interpretive choices. Achieving a compelling performance of Debussy’s French vocal music requires balancing poetic understanding, fidelity to the composer’s vision, and personal artistic individuality. Future exploration should further address the balance between interpretive freedom and stylistic accuracy, as well as the pedagogical strategies that help singers overcome linguistic and expressive challenges in non-native repertoireThe prospects for further research on this issue include the detailed study of the creative heritage of the founders of ensembles, the detection and analysis of all periods of the ensembles’ activity with a focus on the present, and the identification of changes in the consciousness of national identity that occurred in the context of the history of the formation of these ensembles.